Bio equivalence Study of Atorvastatin Tablets - Koytchev, Rossen; Ozalp, Yildiz; Erenmemisoglu, Aydin; Meer, Mike John van der; Alpan, Recep Serdar (Arzneimittelforschung, 2004)
The study was designed to evaluate the relative bioavailability of two formulations of atorvastatin (CAS 134523-03-8). A bioequivalence study was carried out in 24 healthy male volunteers who received four 10 mg tablets of the test formulation (Kolestor®) and the same dose of the originator product. The trial was performed according to an open, crossover design with a wash-out period of 7 days in one study center. Blood samples were taken up to 48 h post dose, the plasma was separated and the concentrations of atorvastatin were determined by HPLC-MS-MS method. The mean Cmax were 16.37 ng/mL and 17.05 ng/mL, while the mean AUC0–t were 103.61 ng · h/mL and 102.55 ng · h/mL for the test and reference formulations, respectively. The mean AUC0–inf were 118.10 ng · h/mL and 117.13 ng · h/mL for the test and reference formulations, respectively. The median tmax was 0.67 h for both the test tablet and the reference product. The mean t1/2 el was 11.85 h for the test formulation and 13.28 h for the reference formulation. No significant differences of pharmacokinetic parameters between the two studied formulations were found. The 90 % confidence intervals for the primary target parameters, intra-individual ratios of AUC0–t and Cmax of atorvastatin, were between 0.85 and 1.05 (AUC0–t) and between 0.84 and 1.23 (Cmax), respectively, and thus within the acceptance ranges. Concerning the secondary parameter tmax the 90 % confidence interval for the intra-individual differences was between -0.17 and 0.17 h. In the light of the present study it can be concluded that the two evaluated atorvastatin formulations, i.e. test formulation of atorvastatin and reference preparation are bioe-quivalent in terms of the rate and extent of absorption.
Keywords: Atorvastatin, bioequivalence, clinical pharmacokinetics; CAS 134523-03-8; Kolestor®